System productivity, energetics and economics of soybean (Glycine max)-wheat (Triticum aestivum) cropping system as influenced by weed management practices - DUBEY, R P; LAL, SHYAM; GHOSH, DIBAKAR; SINGH, P K (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted during 2015–16 and 2016–17 to assess the system productivity, energetics and economics of weed management practices in soybean (Glycine max L.)-wheat (Triticum aestivum L.) cropping system at ICAR-Directorate of Weed Research, Jabalpur, Madhya Pradesh. The experiment comprised 10 treatments having combinations of sole and sequential application of pre-emergence and post-emergence herbicides in both the crops, and their integration with hand weeding undertaken in randomized block design replicated thrice. The highest system productivity (8.04 t/ha) was obtained by employing two hand weedings, sequential application of pendimethalin followed by (fb) imazethapyr in soybean and pendimethalin fb mesosulfuron + iodosulfuron in wheat as well as by integrating either pre or post-emergence herbicides with one hand weeding. Among weed management practices, energy requirement was lowest in sole post-emergence herbicide treatment, however, integration of manual weeding required maximum energy. The energy input for hand weeding was a major share of integrated weed management practices, and it varied from 54–83% of the total treatment energy. Due to requirement of less energy for sole post-emergence herbicides, energy output, net energy return and energy ratio were the maximum. Total output energy was higher (258×103 MJ/ ha) in post-emergence herbicide fb hand weeding treatment because of higher system productivity (7.29 t/ha), and this treatment was more energy efficient and gave the highest economic returns among the weed management practices. The highest benefit: cost ratio (3.10) was obtained by the application of post-emergence herbicides in both the crops.